Novel Synthetic Industrial Approach for Efficient Synthesis of Baclofen through C–C Bond Formation - Raut, Changdev; Qureshi, Shafiya Kausar; Kadam, Nitin; Mungase, Kailas; Marepu, Nagaraju; Jagtap, Ashutosh; Ambhaikar, Narendra (Synlett, 2024)
Baclofen is an active pharmaceutical ingredient used for the treatment of muscle spasticity. We describe our efforts to develop a novel synthetic approach through C–C bond formation and a cost-effective route to baclofen. The synthesis involved a two-step approach through C–C bond formation using the extensively and commercially available starting material 4-chlorobenzyl cyanide with chloroacetic acid as a reagent in an aprotic solvent, followed by reduction of the nitrile functional group. The synthetic route to baclofen has been demonstrated to be commercially viable, cost-effective, and environmentally friendly. Execution of the developed process led to the isolation of (+)-baclofen in an overall yield of 60% at a multikilogram scale with >99.5% HPLC purity. This article also discusses the cost-effectiveness of the process, the impurity profiling, and the product quality.
Keywords: baclofen; C-alkylation; medicinal chemistry; green chemistry